FACTORS INFLUENCING THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN IN THE WORKING AREA OF THE MPUNDA HEALTH CENTER - Alfarabiatun; Darmin; Iwansyah, Aris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Anemia during pregnancy remains a major public health problem because it contributes to increased maternal and neonatal morbidity and mortality. This study aimed to determine the factors associated with the incidence of anemia among pregnant women in the working area of Mpunda Public Health Center, Bima City. This research employed a quantitative analytical design with a cross-sectional approach. The study involved 55 pregnant women selected using purposive sampling. Data were collected through structured questionnaires assessing nutritional intake, adherence to iron tablet consumption, economic status, educational level, and maternal knowledge, while anemia status was determined from hemoglobin examination records. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of 0.05. The results showed that 37 respondents (67.3%) had mild anemia and 18 respondents (32.7%) had moderate anemia. Statistical analysis indicated significant associations between nutritional intake (p = 0.003), adherence to iron tablet consumption (p < 0.05), economic status (p < 0.05), educational level (p < 0.05), and maternal knowledge (p < 0.05) with the incidence of anemia among pregnant women. Poor nutritional intake, low adherence to iron supplementation, low economic status, limited educational attainment, and inadequate maternal knowledge were identified as important factors associated with anemia. Strengthening antenatal care through nutrition education, improved adherence to iron supplementation, and continuous health promotion is recommended to reduce the prevalence of anemia among pregnant women in the Mpunda Public Health Center working area.